2011
DOI: 10.1111/j.1467-9957.2009.02168.x
|View full text |Cite
|
Sign up to set email alerts
|

Public Expenditures, Bureaucratic Corruption and Economic Development*

Abstract: We present a dynamic general equilibrium analysis of public sector corruption and economic growth. In an economy with government intervention and capital accumulation, state-appointed bureaucrats are responsibile for procuring public goods which contribute to productive efficiency. Corruption arises because of an opportunity for bureaucrats to appropriate public funds by misinforming the government about the cost and quality of public goods provision. The incentive for each bureaucrat to do this depends on eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 49 publications
1
42
2
1
Order By: Relevance
“…Nowadays, the TI corruption index is a relatively common institutional measure in the literature, for example, among others Wei (2000), Gyimah-Brembong (2002), Ng and Yeats (1999), Sandholtz and Koetzle (2000) and Torrez (2002). In particular, the TI index has been used by various studies to investigate the effects of corruption on public investment and public infrastructure (Goldsmith, 1999;Blackburn et al, 2011), economic growth, the shadow economy (Pellegrini and Gerlagh, 2004;Buehn and Schneider, 2009) and foreign direct investment (Barassi and Zhou, 2012;Habib and Zurawicki, 2002;Fons, 1999) (Table 1).…”
Section: Fgls =( Xmentioning
confidence: 99%
“…Nowadays, the TI corruption index is a relatively common institutional measure in the literature, for example, among others Wei (2000), Gyimah-Brembong (2002), Ng and Yeats (1999), Sandholtz and Koetzle (2000) and Torrez (2002). In particular, the TI index has been used by various studies to investigate the effects of corruption on public investment and public infrastructure (Goldsmith, 1999;Blackburn et al, 2011), economic growth, the shadow economy (Pellegrini and Gerlagh, 2004;Buehn and Schneider, 2009) and foreign direct investment (Barassi and Zhou, 2012;Habib and Zurawicki, 2002;Fons, 1999) (Table 1).…”
Section: Fgls =( Xmentioning
confidence: 99%
“…Emanuel Anoruo and Habtu Braha (2005) showed that corruption directly negates economic growth by lowering productivity and indirectly by hampering investment. Blackburn et al (2011) argue that corruption distorts the quantity and quality of public expenditures. It means that these expenditures are not only infl ated, but also misdirected towards the provision of low-quality public goods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…5 This is a variant of the elite capture literature, one in which the local elite is not merely a socially or economically higher-status person, but also carries the function of a public official. Allocation of public money has been examined as an outcome of the interaction between politicians and the bureaucracy, where bureaucrats have been modelled as 'professionals' who evaluate public expenditure proposals based on their technical quality or merits (Ting, 2012), as budget-maximisers who seek to have public goods supplied in large quantity (Niskanen, 1971), or as agents who seek to maximise the difference between the quantity of public goods claimed to have, and actually have, provided, retaining this difference as private income (Blackburn et al, 2011).…”
Section: Agents' Incentives and Constraints Direct Decision Makers Inmentioning
confidence: 99%